2020
DOI: 10.20886/ijfr.2020.7.2.113-120
|View full text |Cite
|
Sign up to set email alerts
|

STORAGE TECHNIQUES OF CEMPAKA WASIAN (Magnolia tsiampaca (Miq.) Dandy) SEEDS

Abstract: Cempaka wasian is a type of woody tree which has a substantial historical value associated with the local culture of the Minahasan people. The improvement of cempaka wasian plantation is essential due to their enormous importance and usage. This study aims to discover the impacts of duration, storage room, and containers used for the appropriate storage of cempaka wasian seeds. The design used in this study is entirely randomized design organized with a factorial pattern which consists of 3 factors; 1) storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Several research results showed a decrease in seed viability along with increasing storage time, among others, seeds of kilemo [3] and campaka waisan [4]. Seed quality will decline naturally, as Siahaan [5] stated that seed quality will decrease linearly with time.…”
Section: Introductionmentioning
confidence: 99%
“…Several research results showed a decrease in seed viability along with increasing storage time, among others, seeds of kilemo [3] and campaka waisan [4]. Seed quality will decline naturally, as Siahaan [5] stated that seed quality will decrease linearly with time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the optimal light intensity is needed for maximum growth. Shade utilization is expected to reduce evaporation and transpiration so that the media's humidity can be maintained (Irawan & Hidayah, 2017).…”
Section: Introductionmentioning
confidence: 99%